Analysis of Dusturiyah Policy on the Implementation of Permanent Daytime Running Light/Lamp Regulations by Bogor Police - Fachri Muhammad Aji; Lutfi Fahrul Rizal; Taufiq Alamsyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research analyzes the implementation of the rule requiring motorcyclists to turn on their headlights during the day from the perspective of siyasah dusturiyah. The purpose of this research is to find out the stages of implementation of turning on the headlights of motorcycles during the day from year to year and the impact of the implementation of this regulation in Bogor Regency. The research method used in this research is a case study method with an empirical legal approach. The data analysis technique in this research uses a mixed method, in which the data in this research is taken qualitatively and quantitatively and then described descriptively to draw conclusions. The results showed that when this regulation was first socialized, many people in Bogor Regency rejected and ignored the existence of this regulation, but over time the community has been much more orderly and accepting, although some people are still indifferent. The socialization carried out by Satlantas Polres Bogor is also almost declared successful because most people know this rule even though there are a small number of people who think that this rule has not been socialized properly. The impact of this rule is also positive, which is a decrease in the number of accidents after the implementation of this rule. The siyasah dusturiyah analysis of this rule shows that this rule is in line with the objectives of maqashid sharia where the focus of this rule is to preserve lives and property. This is in line with the principle of siyasah dusturiyah which prioritizes the benefit of the people.